Causal associations between gut microbiota, metabolites, and idiopathic normal pressure hydrocephalus: a two‑sample Mendelian randomization study - Wencai Wang; Menghao Liu; Zun Wang; Luyao Ma; Yongqiang Zhao; Wei Ye; Xianfeng Li (BMC Neurology)
Abstract Background Implying connections with gut microbiome and serum metabolites, idiopathic normal pressure hydrocephalus (INPH) emerges as a prevalent neuropsychiatric condition in the elderly. Our objective was to systematically evaluate the potential causality between gut microbiome, derived metabolites, and INPH through the implementation of Mendelian randomization (MR) methodology. Methods We utilized summary data from extensive genome-wide association studies, encompassing 196 gut microbiomes from the MiBioGen consortium (n = 18,340), 486 serum metabolites from the KORA and TwinsUK studies (n = 7,824), and individuals with INPH (case = 767, control = 375,610), for MR causal estimates. The leading analysis utilized the inverse-variance weighted (IVW) method, supplemented by weighted mode, MR-Egger, weighted median and simple mode approaches. Sensitivity analyses included MR-Egger intercept, Cochran’s Q test, leave-one-out analysis and MR-PRESSO. Results Our study primarily relied on the IVW method, confirming a causality between 9 genetically predicted abundance of gut microbiomes and INPH. We found an adverse correlation with genetically predicted abundance of order Clostridiales, genus Eubacteriumeligensgroup, genus Gordonibacter, genus Ruminococcus1 concerning INPH. Conversely, class Melainabacteria, genus Eubacteriumruminantiumgroup, genus Adlercreutzia, genus Dialister, genus RikenellaceaeRC9gutgroup potentially correlated with increased INPH risk. As for derived metabolites, IVW estimates indicated a causal connection between 25 genetically predicted serum metabolites and INPH. Sensitivity analysis underscored the robustness of our findings. Conclusion Our MR analysis provides evidence supporting the causality of certain gut microbial taxa and their derived metabolites on INPH. This underscores the potential for interventions targeting specific gut microbiota and derived metabolites in the treatment and prevention of INPH.